Hardware and software platform for Internet of Things - Bregell, Johan (My University, 2015)
Internet of Things is a relatively new and undiscovered field under constant change. Today several similar technologies exist, all competing to be accepted as the new standard. As the concept of Internet of Things spans from hardware, to operating system, all the way up to application level communication protocol, this project investigated the most promising technologies in each of these areas. The findings of this investigation were used to build a prototype; this prototype was then used to assess the range, response time, connection speed, and power consumption, of the selected communication protocol. The assessment chapter compares the results to the theoretical values and highlights the differences, while the discussion chapter explores why these differences occur. The obtained results give insight in what kind of applications Internet of Things might bring, and also what issues that currently exist. Amongst the discoveries is the poor response time of an Internet of Things system while using power saving measures. These measures are needed to achieve a battery life of 1 year, resulting in the inability for real-time applications to utilize the power of Internet of Things.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science